Combining NSAM and CPC concentrations to determine airborne nanoparticle count median diameter: Application to various laboratory and workplace aerosols. Issue 6 (3rd June 2018) - Bau, S.; Payet, R.; Toussaint, A.; Witschger, O.; Todea, A.M.; Monz, C.; Asbach, C.
ABSTRACT: Because nanomaterials have been increasingly developed and used in many technology and industry sectors over the last 20 years, an increasing number of workers is likely to be exposed to airborne nanoparticles. In addition, the question of the nanomaterial characteristics that should be assessed in epidemiological studies remains open. Thus, assessing occupational exposure to airborne nanoparticles will not only rely on mass concentration and chemical composition. Rather, key parameters, such as particle size, have to be included in measurement strategies. We previously proposed a methodology to estimate the Count Median Diameter (CMD) of an aerosol based on the simultaneous size-integrated measurement of two particle concentrations, lung-deposited surface area, and number, thanks to field-portable, commercially available aerosol instruments (Nanoparticle Surface Area Monitor/Condensation Particle Counter combination). In addition to previous work, this study investigates the case of various polydisperse metal oxides, organic oil, and salt particles with CMDs ranging from 16–410 nm. Once corrected, the CMDs derived from the NSAM/CPC agree within ±20% with regard to the reference electrical mobility equivalent diameter, regardless of aerosol composition, morphology, or geometric standard deviation (GSD). Furthermore, the field-applicability of the method was tested through 6 sets of experimental data stemming from workplace measurement campaigns where different materials were produced and handled (TiO2, SiO2, Ag, Multi-Walled Carbon Nanotubes—MWCNT), covering a range of CMDs between 40 and 190 nm. All situations considered, the approach based on the combination of a NSAM and a CPC leads to a satisfying estimation of particle CMD, within ±20% compared to reference CMD.